Suicidal behaviours among 13- to 15-year-olds in four southeast Asian countries: Trends and contributing factors - Thach Tran; Hau Nguyen; Jane Fisher (Cambridge Prisms: Global Mental Health, 2025)
This study aimed to describe changes over time in the prevalence and associated factors of suicidal behaviours among 13– to 15–year–olds in Southeast Asian countries. It is a secondary analysis of cross-sectional data from the Global School-based Student Health Surveys conducted in Indonesia, Myanmar, the Philippines and Thailand in 2007/2008 and 2015/2016. Each survey included a nationally representative sample of students aged 13–15 years. Data on suicidal thoughts, plans, attempts, and associated factors—including health risk behaviours, experiences of physical violence and bullying, social difficulties, and parental supervision—were collected using self-report questionnaires. The population attributable fraction for each risk factor was calculated using multiple logistic regression. The prevalence of suicidal behaviours ranged from 0.7% (Myanmar) to 17.3% (Philippines) in 2007/2008, and from 8.6% (Indonesia) to 20.9% (Thailand) in 2015/2016. Being physically attacked or bullied and experiencing social difficulties were the most consistent and significant risk factors across countries and time points. Female gender, poverty, alcohol consumption, and drug use also contributed to risk at varying levels. Suicidal behaviours have risen alarmingly in several Southeast Asian countries. These findings suggest the urgent need for coordinated action by policymakers, health professionals, educators, and families to prevent adolescent suicidal behaviours.